The quest for effective regulation of Islamic money market: an appraisal of the applicable laws in Malaysia - Olayemi, Abdul Azeez Maruf; Hasan, Aznan; Ibrahim, Uzaimah; Yasin, Marifatul Haq; Mahamoud, Siti Mashitoh; Buang, Ahmad Hidayat (Journal of Islamic Legal Studies, 2016)
The absence of an effective framework for the regulation of Islamic money market in many jurisdictions is inhibiting the growth of the Islamic finance. This study aims to suggest a way out of the logjam. It appraises the regulatory framework of the Malaysian Islamic Money Market which is believed to be the most developed in the world. The fabric of the framework is comprised of codified Shariah principles that are required for the compliance of the Market with Shariah, as well as the statutory guidelines, rules and notes that governs the activities of the market. It can be asserted that Malaysian framework is comparable to the conventional money market framework in terms of efficiency, reliability and viability. Therefore, the study concludes that the espousal of the framework as the best practice model in the emerging jurisdictions will go a long way in helping to surmount the challenges.